2022
DOI: 10.3390/su14159572
|View full text |Cite
|
Sign up to set email alerts
|

Destination Promotion through Images: Exploring Tourists′ Emotions and Their Impact on Behavioral Intentions

Abstract: Tourists are increasingly looking for more emotion in the promotion of destinations in order to make decisions about their holidays. Traditional promotional tools centred on images have advantages over other sensorial tools due to the consumer′s knowledge of them. Nevertheless, simultaneously, the continued use of images leads to the sophistication of the receiver, making it necessary to analyse their capacity to create emotions and their effects. The main objective of this study is to evaluate consumers′ emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…GSR is the third most common, used alone in two studies and five times in combination with other modalities such as EMG, FAC, EEG, ET, and HR. For instance, Di-Clemente et al [ 33 ] used GSR on 38 participants to assess their immediate emotional reactions to images advertising travel locations. Boz et al [ 57 ] also used GSR together with EEG, ET, and HR to examine how travelers view pricing in holiday advertisements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GSR is the third most common, used alone in two studies and five times in combination with other modalities such as EMG, FAC, EEG, ET, and HR. For instance, Di-Clemente et al [ 33 ] used GSR on 38 participants to assess their immediate emotional reactions to images advertising travel locations. Boz et al [ 57 ] also used GSR together with EEG, ET, and HR to examine how travelers view pricing in holiday advertisements.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, images from the cities of Bruges and Kyoto were employed in the EEG study for the identification of travel preferences [ 21 ]. Additionally, in the GSR experiment, images of Egypt and the Caribbean were utilized with various typologies for the same goal—to identify preferences for locations [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the framework of the SOR model, emotion, as an organism, contributes to consumers' willingness to purchase online and tourists' intention to visit a destination (Thomas and Mathew 2018;Li et al 2022). In several different studies, pleasure, arousal and admiration were confirmed to influence audiences' willingness or behaviour to participate in film tourism (Im and Chon 2008;Yen and Croy 2013;Di-Clemente et al 2022). Therefore, this research categorises emotion into pleasure, arousal and admiration emotions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The theoretical research on EGIS has been focused on the development of frameworks that integrate emotions in GIS, while the practical applications have been focused on the implementation of EGIS in various domains, such as urban planning, transportation, tourism, and environmental management. In the tourism industry, EGIS can help to develop more personalized and emotionally engaging travel experiences by incorporating information about the emotional responses of tourists to different destinations [36,39,40].…”
Section: Place Attachment Mapping and Emotional Gismentioning
confidence: 99%